MANAGEMENT OF RISK SITUATIONS - Desislava Todorova; Tsvetelina Mihaylova; Rumiana Etova; Svetoslav Garov (Peytchinski Publishing, 2016)
Risk is the probability of an event occurrence at a certain moment with a negative impact on the population, territory, environment, cultural values and material valuables. The management of risk situations is necessary for any organization in which unforeseen circumstances may arise. The management of risk situations includes quantitatively expressing risk and its manifestation; risk assessment and risk analysis. Effectiveness in dealing with risky situation coordination is needed to be established between the management vertical and horizontal structures in the State. Preventing, controlling and overcoming the consequences impose an integral process of management and planning events. The requirements for growing professionalism in the management of all levels are obvious.